2017
DOI: 10.1002/anie.201705018
|View full text |Cite
|
Sign up to set email alerts
|

Steering Surface Reaction Dynamics with a Self‐Assembly Strategy: Ullmann Coupling on Metal Surfaces

Abstract: Ullmann coupling of 4-bromobiphenyl thermally catalyzed on Ag(111), Cu(111), and Cu(100) surfaces was scrutinized by scanning tunneling microscopy as well as theoretical calculations. Detailed experimental evidence showed that initial formation of organometallic intermediates on the surface, as self-assembled structures or sparsely dispersed species, is determined by the subsequent reaction pathway. Specifically, the assembled organometallic intermediates at full coverage underwent a single-barrier process to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 42 publications
5
67
0
Order By: Relevance
“…[30][31][32] In addition, additives have been used to supress acertain reaction [33,34] and preorganization by different self-assembled structures has been shownt oi nfluencet he reactivity. [35,36] Alternatively, one can run the process at different coverages [37][38][39] or temperatures [40] and use these readily varied reactionp arameters for product control.H owever, to date only few exampleso nr eactionc ontrol based on surfacec overage in two-dimensionalc hemistry have been reported. [41] Herein, we show that the surfacec overage of 6-ethynyl-2naphthoic acid (ENA 1,i ts synthesis is described in the Supporting Information) steers reaction outcomeo nt he Ag(111) substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32] In addition, additives have been used to supress acertain reaction [33,34] and preorganization by different self-assembled structures has been shownt oi nfluencet he reactivity. [35,36] Alternatively, one can run the process at different coverages [37][38][39] or temperatures [40] and use these readily varied reactionp arameters for product control.H owever, to date only few exampleso nr eactionc ontrol based on surfacec overage in two-dimensionalc hemistry have been reported. [41] Herein, we show that the surfacec overage of 6-ethynyl-2naphthoic acid (ENA 1,i ts synthesis is described in the Supporting Information) steers reaction outcomeo nt he Ag(111) substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Also protective group strategies that are well established in solution‐phase chemistry have been developed . In addition, additives have been used to supress a certain reaction and preorganization by different self‐assembled structures has been shown to influence the reactivity . Alternatively, one can run the process at different coverages or temperatures and use these readily varied reaction parameters for product control.…”
Section: Introductionmentioning
confidence: 99%
“…showed the complete pathway of Ullmann coupling by STM and AFM. In the same year, Zhou et al. reported that the reaction pathway is influenced by whether the initially formed organometallic intermediate self‐assembled or not.…”
Section: C−x and C−h Activation Of Sp2‐carbonmentioning
confidence: 99%
“…The self‐assembly strategy can also be utilized to change the reaction pathway via the formations of various reaction intermediates. A typical case is the Ullmann coupling of 4‐bromobiphenyl (BBP, C 6 H 5 C 6 H 4 Br) on Ag(111) . After being deposited on Ag(111) at low temperature and then warmed up to room temperature, the BBP molecules are transformed into Ag‐coordinated organometallic intermediates, C 6 H 5 C 6 H 4 AgC 6 H 4 C 6 H 5 (Ag‐COI).…”
Section: Controlling Surface Reaction Via Molecular Manipulationmentioning
confidence: 99%
“…Color bar (m): apparent height in the STM images. a–m) Reproduced with permission . Copyright 2017, Wiley‐VCH.…”
Section: Controlling Surface Reaction Via Molecular Manipulationmentioning
confidence: 99%